Development of Creative Problem Solving (CPS)-Based Articulate Storyline Media to Develop Students' Creative Thinking Ability SPLDV Class VIII Material - Victorio Isya Erlangga; Baiduri Baiduri; Mayang Dintarini (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This study aims to develop Articulate Storyline learning media based on Creative Problem Solving (CPS) to develop students' creative thinking skills in grade VIII SPLDV materials in a valid, practical and effective manner. The development model used in this research is the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate). This research was conducted on class VIII students of Middle School. The data analysis technique used in this study is the validity, practicality and effectiveness analysis of the media. The results showed that for the acquisition of scores from media experts it was 94% with very valid criteria, then for the acquisition of an average score from material experts it was 100% with very valid criteria, and for the practicality of the media it was obtained from the acquisition of scores from student response questionnaires that were equal to 85.5% with very practical criteria. The use of this media also affects the improvement of students' creative thinking abilities, this can be shown from the results of the N-Gain test that has been carried out, where the score obtained is 0.7541, which is > 0.7 which is included in the high criteria. These results indicate that the developed Articulate Storyline based Creative Problem Solving (CPS) media includes valid, practical and effective criteria for developing students' creative thinking abilities.